Spatial zoning and spatial analysis of urban poverty using spatial analysis (Case study: Mashhad city) - Hadi Soleimani moghadam; rahman zandi; ebrahim akbari (تحقیقات کاربردی علوم جغرافیایی)
Spatial Zoning and Analysis of Urban Poverty via Spatial Analysis (Case Study: Mashhad City)